Discrepant Dimensions of Belonging in Nathacha Appanah’s Tropic of Violence - Theron, Cleo Beth (Research in African literatures, 2024)
This article offers a reading of the novel Tropic of Violence by Nathacha Appanah that attends to the question of belonging. The article aims to contribute to criticism of literary depictions of migration within the Indian Ocean and draws on the unique migratory and population dynamics of the island of Mayotte in the Comoros, an archipelago off the east coast of Africa. The article addresses the affective, social, and political dimensions of belonging regarding three thematic aspects of the novel: firstly, mobility, discussing the discrepancies between the movement and access of French metropolitans in comparison to Comoran migrants; secondly, the imbrication of various social and political identities—Mahoran, Comoran, and French—that characterizes the island’s population and influences islanders’ quality of life; and thirdly, place attachment, noting the parallels drawn between environmental degradation and social pressures and how landscapes in the novel register a loss of belonging.